Analysis of the Relationship Between Second Zagreb Index Values and the Oxidation Levels of Terpenoid Derivatives - Luzianawati Luzianawati; Muhammad Ahsan Hidayat; Ni Komang Tri Dharmayani; I Gede Adhitya Wisnu Wardhana (Eigen Mathematics Journal, 2025)
Terpenoids are a group of secondary metabolites composed of isoprene units containing five carbon atoms (C5), synthesized from acetate through the mevalonate pathway. This research examines two triterpenoid derivatives, densiflorinic acid A and densiflorinic acid B. The second Zagreb index is applied to illustrate atomic interaction patterns—including H--C, C--O, O--H, and C--C—which serve as indicators of molecular structural complexity. The findings indicate that the second Zagreb index is a reliable measure for assessing the structural complexity and oxidation levels of triterpenoid derivatives that share the same core framework.